2018
DOI: 10.5114/pg.2018.75824
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chosen cell cycle and proliferation markers in pancreatic intraepithelial neoplasia

Abstract: IntroductionPancreatic ductal adenocarcinoma is one of the most aggressive tumours that develops from precursor lesions, most frequently including pancreatic intraepithelial neoplasia (PanIN). Deregulation of the cell cycle, responsible for uncontrolled cell proliferation, is an important phenomenon in the development of this cancer.AimTo evaluate the cell cycle and the expression of proliferation markers, namely Ki67, PCNA, and cyclin D1 in pancreatic intraepithelial neoplasia at its different stages of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…4a, b ). However, this might reflect the differential tumour progression in 1SKO/R and pDKO/R animals as positive Ki67 staining has been shown to increase with lesion grade 37 , 38 . To identify molecular alterations in primary ductal tumour cells, we first examined the activation status of NF-κB and Ral signalling via fluorescence-activated cell sorting (FACS) staining for phospho-NF-κB/p65 or phospho-TBK1 (TANK-binding kinase-1) as readouts for the respective pathways.…”
Section: Resultsmentioning
confidence: 99%
“…4a, b ). However, this might reflect the differential tumour progression in 1SKO/R and pDKO/R animals as positive Ki67 staining has been shown to increase with lesion grade 37 , 38 . To identify molecular alterations in primary ductal tumour cells, we first examined the activation status of NF-κB and Ral signalling via fluorescence-activated cell sorting (FACS) staining for phospho-NF-κB/p65 or phospho-TBK1 (TANK-binding kinase-1) as readouts for the respective pathways.…”
Section: Resultsmentioning
confidence: 99%
“…3D). Previous reports indicated that cyclin D1 and PCNA are involved in cell cycle control (21) and that p27 is a cyclin-dependent kinase inhibitor (22); these genes are thus markers of cell proliferation. Thus, mRNA levels of PCNA, cyclin D1, and p27 were evaluated via RT-qPCR.…”
Section: Overexpression Of Usp19 Inhibits Ccrcc Cell Proliferation Inmentioning
confidence: 99%
“…In a study by Chen et al elevated CAIX amounts were shown to promote tumor progression ( 34 ). Furthermore, the proliferation antigen Ki67 is closely associated with cell mitosis, playing a vital role in the initiation of cell proliferation ( 35 ). Proliferating cell nuclear antigen (PCNA) is an important trigger of multiple events in DNA replication, repair and recombination in eukaryotes and archaea, thus regulating cell proliferation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%